Effects of Hydrotherapy on Postural Control of Women with Fibromyalgia Syndrome: A Single Arm Study. Issue 3 (2nd October 2015) - Trevisan, Deborah Colucci; Avila, Mariana Arias; Driusso, Patricia; Gramani-Say, Karina; Araujo-Moreira, Fernando M.; Parizotto, Nivaldo Antonio
Abstract: Objective: To evaluate the effects of a 16-week program of hydrotherapy on postural control and pain of women with fibromyalgia syndrome [FMS]. Methods: Seventeen women with FMS performed three evaluation sessions, one before, one in the middle and one at the end of a 16-week hydrotherapy treatment program. The outcome measure was postural control of the body during quiet erect posture on upright stance [eyes opened and closed] and right and left tandem on a force platform. Pain was evaluated with the Visual Analogue Scale [VAS] and function with the Fibromyalgia Impact Questionnaire [FIQ]. Statistical analysis was performed with Friedman's ANOVA and Wilcoxon's matched pairs test. Effect sizes were measured with Cohen's d coefficient. For all variables, a level of 5% of significance was adopted. Results: Postural control showed decreased variables, especially for the right and left tandem positions with eyes closed and opened. Pain and function also showed improvement after 8 and 16 weeks of hydrotherapy treatment. Conclusions: Hydrotherapy was effective in improving postural control, pain and function in women with FMS.